The State of Social Enterprise and Opportunities for Sustainable Development in the Global South: A Critical Literature Review - Samuel Ebie (Innovation and Entrepreneurship Research in the Global South 1st International Research Symposium, Swansea University [HYBRID], 2024)
This critical literature review investigates the current condition of social enterprise and its potential to promote sustainable development in the global south. The review identifies key themes by conducting a thematic analysis of recent and relevant literature, such as the role of social enterprises in addressing socioeconomic challenges, the impact of policy environments, and the influence of local cultures and community engagement on social enterprise success. It also looks at the challenges that social organisations/firms confront, such as limited access to funding and poor institutional support. The review focuses on the convergence of social enterprise and Sustainable Development Goals (SDGs), stressing how innovative business models can promote equitable growth and environmental sustainability. The research sheds light on the situation, difficulties, and prospects facing social entrepreneurs as they work to promote sustainable development in the Global South.